Antifungal activities of secondary metabolites isolated from liquid fermentations of Stereum hirsutum (Sh134-11) against Botrytis cinerea (grey mould agent). (November 2017) - Aqueveque, Pedro; Céspedes, Carlos L.; Becerra, José; Aranda, Mario; Sterner, Olov
Abstract: Extracts obtained from liquid mycelial fermentations of the Chilean fungus Stereum hirsutum (Sh134-11) showed antifungal activity against Botrytis cinerea. Two types of extracts were obtained: EtOAc-extract (liquid phase) and MeOH-extract (mycelial phase). Plate diffusion assay showed that EtOAc-extracts were more active than MeOH-extracts. A large-scale fermentation of Sh134-11 and chromatographic methods allowed to isolated four compounds: MS-3, Vibralactone, Vibralactone B and Sterenin D. Only Sterenin D showed antifungal activity against B. cinerea in the tests performed. Effects on the mycelial growth of B. cinerea showed that Sterenin D showed inhibition at 1000–2000 μg/mL reaching 67% and 76% respectively. Sterenin D was more effective to control the sporogenesis, inhibiting in 96% the sporulation at 500 μg/mL. Assays showed that Sterenin D exhibited a minimal fungicidal concentration (MFC) of 50 μg/mL and minimal inhibitory concentration (MIC) at 20 μg/mL. Our study indicated that submerged fermentations of Chilean S. hirsutum (Sh134-11) produced extracts with antifungal activity and Sterenin D is responsible for this activity, which could be used as possible biofungicides alternative to synthetic fungicides. Graphical abstract: Highlights: Large-scale fermentation of Chilean fungus S. hirsutum (Sh-134-11) produced active extracts against B. cinerea. Bioassay-guided fractionation allowed to identify 4 compounds: MS-3, Vibralactone, Vibralactone B and Sterenin D. Only sterenin D showed antifungal activity inhibiting mycelial growth and sporogenesis of B. cinerea. Sterenin D showed MIC and MFC values at 10 and 50 μg/mL against B. cinerea respectively.